2019
DOI: 10.1037/xlm0000614
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions of the process-dissociation procedure are violated in implicit sequence learning.

Abstract: In implicit sequence learning, a process-dissociation (PD) approach has been proposed to dissociate implicit and explicit learning processes. Applied to the popular generation task, participants perform two different task versions: instructions require generating the transitions that form the learned sequence; instructions require generating transitions other than those of the learned sequence. Whereas accurate performance under inclusion may be based on either implicit or explicit knowledge, avoiding to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…When we focus on quantifying subjective experience, all measures will face interpretational complications. As such, it has been previously suggested in memory research and sequence learning that subjects may fail to perform exclusion and inclusion reliably (Dodson & Johnson, 1996;Graf & Komatsu, 1994)either as a result of not understanding the instructions or because of the complexity of the instructions-or they may use different strategies for exclusion and inclusion leading to distorted estimates of explicit and implicit processes (Barth, Stahl, & Haider, 2019). Failure to exclude and/or include may then lead to biased estimates of the AI.…”
Section: Discussionmentioning
confidence: 99%
“…When we focus on quantifying subjective experience, all measures will face interpretational complications. As such, it has been previously suggested in memory research and sequence learning that subjects may fail to perform exclusion and inclusion reliably (Dodson & Johnson, 1996;Graf & Komatsu, 1994)either as a result of not understanding the instructions or because of the complexity of the instructions-or they may use different strategies for exclusion and inclusion leading to distorted estimates of explicit and implicit processes (Barth, Stahl, & Haider, 2019). Failure to exclude and/or include may then lead to biased estimates of the AI.…”
Section: Discussionmentioning
confidence: 99%
“…It may provide a relevant alternative to existing PDP generation tasks. Inded, addressing the pitfalls in PDP methodology has continuously received considerable attention (Barth et al, 2019;Fu et al, 2018;Hirshman, 2004;Norman, 2015;Norman et al, 2007;Pasquali et al, 2019;Stahl et al, 2015). The need for refining the PDP task is underscored by its relevance to addressing major theoretical questions in the field.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that introducing a probabilistic component to an event sequence can minimize the level of awareness associated with the newly acquired knowledge (Rosenthal et al, 2009 ; Vandenberghe et al, 2006 ). However, the empirical foundation on which to base a lack of conscious awareness remains an open question (Barth et al, 2019 ; Cleeremans & Jimenez, 1998 ; Destrebecqz & Cleeremans, 2001 ; Hannula et al, 2023 ; Rosenthal & Soto, 2016 , 2016 ; Rosenthal et al, 2009 , 2013 ; Shanks & John, 1994 ; Shanks & Johnstone, 1999 ; Soto et al, 2019 ; Vadillo et al, 2016 , 2022 ). Thus, when learning visible event sequences, we restrict the term implicit so that it refers to learning regularities under conditions where a participant is not oriented to the presence of the embedded regularities.…”
mentioning
confidence: 99%